Cell culture density affects the proliferation activity of human adipose tissue stem cells. (17th January 2016) - Kim, Dae Seong; Lee, Myoung Woo; Ko, Young Jong; Chun, Yong Hoon; Kim, Hyung Joon; Sung, Ki Woong; Koo, Hong Hoe; Yoo, Keon Hee
Abstract : In this study, we investigated the effect of cell density on the proliferation activity of human mesenchymal stem cells (MSCs) derived from adipose tissue (AT‐MSCs) over time in culture. Passage #4 (P4) and #12 (P12) AT‐MSCs from two donors were plated at a density of 200 (culture condition 1, CC1) or 5000 (culture condition 2, CC2) cells cm −2 . After 7 days of incubation, P4 and P12 AT‐MSCs cultured in CC1 were thin and spindle‐shaped, whereas those cultured in CC2 had extensive cell‐to‐cell contacts and an expanded cell volume. In addition, P4 and P12 AT‐MSCs in CC1 divided more than three times, while those in CC2 divided less than once on average. Flow cytometric analysis using 5(6)‐carboxyfluorescein diacetate N ‐succinimidyl ester dye showed that the fluorescence intensity of AT‐MSCs was lower in CC1 than in CC2. Furthermore, expression of proliferation‐associated genes, such as CDC45L, CDC20A and KIF20A, in P4 AT‐MSCs was higher in CC1 than in CC2, and this difference was also observed in P12 AT‐MSCs. These data demonstrated that cell culture density affects the proliferation activity of MSCs, suggesting that it is feasible to design a strategy to prepare suitable MSCs using specific culture conditions. Copyright © 2016 John Wiley & Sons, Ltd.